1996
DOI: 10.1038/nm0596-574
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the CD95 (APO–1/Fas) receptor/ligand system in drug–induced apoptosis in leukemia cells

Abstract: Cytotoxic drugs used in chemotherapy of leukemias and solid tumors cause apoptosis in target cells. In lymphoid cells the CD95 (APO-1/Fas)/CD95 ligand (CD95-L) system is a key regulator of apoptosis. Here we describe that doxorbicin induces apoptosis via the CD95/CD95-L system in human leukemia T-cell lines. Doxorubicin-induced apoptosis was completely blocked by inhibition of gene expression and protein synthesis. Also, doxorbicin strongly stimulates CD95-L messenger RNA expression in vitro at concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

35
623
5
5

Year Published

1996
1996
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 907 publications
(668 citation statements)
references
References 22 publications
35
623
5
5
Order By: Relevance
“…For this purpose, a number of di erent cell clones were employed, which were either devoid of individual caspases or which expressed proteins interfering with discrete steps of the apoptotic cascade. It has been proposed that the CD95 system is involved in anticancer drug-induced cell death (Friesen et al, 1996;Fulda et al, 1997aFulda et al, ,1998MuÈ ller et al, 1997;Herr et al, 1998). However, we and others have recently demonstrated that anticancer drugs induce apoptosis by a mitochondrial pathway that is independent of death receptors.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…For this purpose, a number of di erent cell clones were employed, which were either devoid of individual caspases or which expressed proteins interfering with discrete steps of the apoptotic cascade. It has been proposed that the CD95 system is involved in anticancer drug-induced cell death (Friesen et al, 1996;Fulda et al, 1997aFulda et al, ,1998MuÈ ller et al, 1997;Herr et al, 1998). However, we and others have recently demonstrated that anticancer drugs induce apoptosis by a mitochondrial pathway that is independent of death receptors.…”
Section: Discussionmentioning
confidence: 83%
“…It has been demonstrated that chemotherapeutic drugs induce the expression of CD95 and CD95L. Therefore, it was proposed that drug-induced apoptosis is mediated in a paracrine or autocrine loop via CD95/CD95L interaction, analogously to T cell receptor-mediated cell death (Friesen et al, 1996;Fulda et al, 1997aFulda et al, , 1998MuÈ ller et al, 1997;Herr et al, 1998;Dhein et al, 1995). However, there are also reports indicating that anticancer drugs induce apoptosis independently of death receptors Wesselborg et al, 1999;Eischen et al, 1997;Gamen et al, 1997;Villunger et al, 1997;Fulda et al, 1997b;Tolomeo et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Injection of anti-Fas MAb into mice carrying lymphoma xenotransplants can induce tumour regression (Coney et al, 1994;Durandy et al, 1997). The Fas/FasL apoptotic pathway may also play a role in the action of chemotherapeutic drugs (Friesen et al, 1996;Landowski et al, 1997). Taken together, these observations suggest that Fas may be involved in the regulation of in vivo lymphoma growth and that Fas triggering may be a promising strategy for treatment of NHLs.…”
mentioning
confidence: 99%
“…Several studies demonstrated that a variety of widely used anticancer drugs kill cancer cells through induction of apoptosis (Walker et al, 1991;Vial et al, 1997), and some authors observed that antineoplastic agents can induce apoptosis through a Fas/ Fas-ligand-dependent pathway (Friesen et al, 1996;Fulda et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Many mechanisms for caspase activation probably exist, but the best documented is that involving several members of the tumour necrosis factor (TNF) family of cytokine receptors including TNF-R1 and Fas (CD95/APO-1) (Nagata & Golstein, 1995). Although, it has been observed that antineoplastic agents can induce apoptosis through a Fas/Fas-ligand-dependent pathway (Friesen et al, 1996;Fulda et al, 1997) currently there are many controversial and diverging opinions about its implication in drug-induced apoptosis and many studies, including our previous observations, indicate that antineoplastic treatments trigger apoptosis through a Fas-independent pathway (Villunger et al, 1997;Eischen et al, 1997;Tolomeo et al, 1998). It is possible that these divergent results could depend on the di erent experimental models used.…”
Section: Introductionmentioning
confidence: 99%